Statistical knowledge: perceptions of High School students in a public school in the city of Caxias, Maranhão - Oliveira, Francinete Sousa de (2021)
This research is the result of work developed with high school students, which aimed to assess students' perception of statistical knowledge, as well as discovering whether the activity contributed to learning these contents. The idea came about by detecting the lack of practices with this purpose. The instrument used to analyze the contributions of the activity, in identifying the perception and learning of Statistics, was a questionnaire and the information obtained was organized in graphs, so that a qualitative quantitative analysis of the information could be carried out, supported by content analysis. The referred activity managed to show that a portion of the researched public did not know Statistics and is unaware of its applicability. Another situation also identified is that students do not see Statistics, which is reduced to mathematical knowledge and which is associated with the most diverse areas of knowledge, in addition to representing the contribution of the activity, in terms of learning about statistical knowledge. Research can provide information that can be used by teaching professionals, and thus offer possible actions that can alleviate the present difficulties in learning Statistics. Thus, this work offers paths on how to carry out interventions that involve statistical knowledge in different areas of knowledge, because the Arco de Maguerez methodology is easily adapted to all fields of knowledge, which undoubtedly can significantly contribute to learning.